PERAN ORIENTASI KEWIRAUSAHAAN DAN ORIENTASI PEMBELAJARAN DALAM MENINGKATKAN KINERJA BISNIS UKM JAWA TENGAH - Sisno Riyoko (Asian Journal of Innovation and Entrepreneurship, 2022)
This research wants to produce hypothesis testers about the role of entrepreneurial orientation and learning orientation on SME business performance. The purpose of this research is to further improve the business performance of SMEs through the application of entrepreneurial orientation and learning orientation. In particular, the research objectives are: 1) Knowing the role of entrepreneurial orientation including a proactive attitude, courage to take risks and learning orientation on SME business performance, 2) To implement research results in the community. To achieve this goal, hypothesis testing was carried out on the independent variables and the dependent variable. The population who became respondents in this study were all owners of SMEs engaged in batik/weaving, totaling 250 business units. While the research sample taken as many as 220 SME owners. The sample was taken based on simple random sampling, where all the population has the opportunity to be a sample. The research approach method used is descriptive and quantitative approaches. The results of the study found that being proactive, risk taking and learning orientation had a significant influence on the business performance of SMEs. This research contributes to the development of an entrepreneurial orientation.